The effect of exercises using a special device (soccer wave) in the development of the skills of some of the high balls skills for young football players aged (17-19) years - Anwar, Saif (Journal of Physical Education, 2019)
The research aims to develop exercises using a special device (soccer wave) intended to develop the high balls skills of football in order to better investment opportunities possible during matches and thus record number of more goals. The problem identified in the weakness of some high balls skills at young players aged (17-19 years), the experimental method was used to sample consisted of (20) players from Youth football players of Azzwraa Club, divided into two unequal experimental and control, has reached a researcher to several conclusions, including that the exercise using a wave or (soccer wave) has led to the development of specific skills games air in the search. The researcher recommended worthwhile to train these skills within the educational and training units football to its importance in achieving good results in the games.